Developing a Collaborative Managerial Supervision Model by Principals to Enhance Instructional Management Quality in Elementary Schools - Sakhriadi Sakhriadi; Alfroki Martha; Weni Yulastri (Journal of Education Research, 2026)
Effective learning management forms the foundation of quality education, but its implementation in primary schools remains inconsistent, particularly in areas with limited administrative oversight. This study explores the role of school principals' managerial supervision in enhancing learning management practices in State Elementary Schools in Gunung Kerinci District. Using a descriptive qualitative approach with a case study design, data were collected through in-depth interviews, structured observations, and document analysis involving principals, teachers, and administrative staff. The data were analyzed using the Miles and Huberman interactive model, which includes stages of data condensation, presentation, and drawing conclusions. The findings reveal that principals who systematically carry out supervisory functions—including planning, monitoring, and providing evaluative feedback—significantly contribute to improving teachers' instructional planning, classroom material delivery, and assessment of learning outcomes. This study concludes that consistent and reflective managerial supervision strengthens the quality of learning and teachers' professional performance, and recommends enhancing capacity development programs for school principals to implement supervision functions at the basic education level.